Cellular AND Gates: Synergistic Recognition to Boost Selective Uptake of Polymeric Nanoassemblies. (15th April 2020) - Gao, Jingjing; Wu, Peidong; Fernandez, Ann; Zhuang, Jiaming; Thayumanavan, S.
Abstract: The development of nanoparticle‐based biomedical applications has been hampered due to undesired off‐target effects. Herein, we outline a cellular AND gate to enhance uptake selectivity, in which a nanoassembly–cell interaction is turned on, only in the concurrent presence of two different protein functions, an enzymatic reaction (alkaline phosphatase, ALP) and a ligand–protein (carbonic anhydrase IX, CA IX) binding event. Selective uptake of nanoassemblies was observed in cells that overexpress both of these proteins (unicellular AND gate). Interestingly, selective uptake can also be achieved in CA IX overexpressed cells, when cocultured with ALP overexpressed cells, where the nanoassembly presumably acts as a mediator for cell–cell communication (bicellular AND gate). This logic‐gated cellular uptake could find use in applications such as tumor imaging or theranostics. Abstract : It′s logical : A cellular AND gate ensures the specific uptake of a polymeric nanoassembly only when two proteins (alkaline phosphatase, ALP, and carbonic anhydrase, CA XI) are present on the cell surface. ALP removes a protecting group from the nanoassembly, exposing the ligand of CA XI, enabling uptake. These proteins can be present on the surface of the same cell (a unicellular AND gate) or on the surfaces of different cells (a bicellular AND gate).